TECHNOLOGY ADOPTION ANALYSIS OF ISLAMIC BANKS MOBILE BANKING IN INDONESIA - Siti Jamilah; Ramadhan, Zulfikar; Yalina, Nita; Nabighah, Mirrah (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2024)
Introduction: The primary objective of this research is to explore customer trust, attitudes, and experience , directly effect on perceived usefulnessas and perceived ease, and indirectly impact on attitude toward using and actual system use, as utilizing Mobile Banking of the 5 Top Brand Award Sharia Banks. Methods: The study employs a quantitative method, focusing on understanding the interrelations between multiple variables. Exerting random sampling of 280 customers from the 5 Top Brand Award Sharia Banks participated as respondents in the study, and data was collected through both questionnaires and secondary sources. Results: The findings from the study indicate that all variables i.e. customer trust, attitude, and experience have a significant effect on perceived usefulness and perceived ease of use. Furthermore, both of them also have significant on attitude toward using and actual system use. Conclusion and suggestion: In summary, the technology adoption and mobile banking use by consumers variables can be explained by the perceived usefulness and perceived ease of use variables. It implicates that customers have confidence that mobile banking provides benefits for customers related to financial transaction solutions. Therefore, Islamic banks have to always update their technology and inform the public how to use it.